A hybrid approach to define and represent material distribution in heterogeneous objects. Issue 1 (2nd January 2017) - Sharma, G.K.; Gurumoorthy, B.
ABSTRACT: A hybrid representation is proposed to overcome the current limitations in modeling heterogeneous objects. The representation is based on the idea of decomposing the geometry such that the existing class of material functions (distance based function) can be used to define desired material variation in heterogeneous objects. This representation is supported by Medial Axis Transform (MAT), which defines and represents the material variation from inside to outside for heterogeneous objects. Local symmetry inherent in the MAT and the relationship between the object boundary and the MAT point has been used to achieve intuitive variations of material composition, local control over the same and a compact data structure. A material evaluation scheme has been proposed to evaluate the material composition at any given location in the object. Heterogeneous objects modeled with this scheme are shown in results depicting the material distribution varying from inside to outside and vice versa. This representation is general to any object because of the existence of a unique MAT for all objects. GRAPHICAL ABSTRACT: